Treatment cost of metastatic colon cancer in Turkey - Kockaya, Guvenc; Polat, Mine; Wertheimer, Albert; Ozet, Ahmet; Malhan, Simten; Vural, İsmail Mert; Akbulat, Akif; Artıran, Guven; Gursoz, Hakkı; Kerman, Saim (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
OBJECTIVES: Colon cancer is the third most common in the top cancer incidence list in Europe. In Europe 212,000 patients die every year due to colon cancer. In Turkey 120,000-130,000 new cancer patients are diagnosed every year, 7.1% of whom are diagnosed to have developed colon cancer. Metastases will occur in up to 50% of the patients who are newly diagnosed. Survival appears to be further prolonged to more than 20 months with new pharmaceuticals; however, these new pharmaceuticals increase the total cost of care. The aim of this study is to estimate the cost implications of new colon cancer treatment options for Turkey.METHODS: Gazi University Hospital treatment protocols for colon cancer treatment were used. Cost of FUFA (5 FU/LV), FOLFIRI, FOLFOX, bevacizumab/FUFA, bevacizumab/FOLFIRI, bevacizumab/FOLFOX, irinotecan and irinotecan/cetixumab protocols were calculated. The cost of combination of protocols were calculated depending on a Markov analysis. The exchange rate was US$ 1 for TL 1.5.RESULTS: Depending on the life expectancy the lowest total cost was established by FUVA (US$ 5,359). It was followed by FOLFIRI then FOLFOX and FOLFOX, US$ 14,144 and US$ 16,553, respectively. The lowest cost for each week of life expectancy was established by FUVA with US$ 98.CONCLUSIONS: Only FUFA, FOLFIRI followed by FOLFIX, FOLFIRI/bevacizumab then FOLFOX then cetuximab, FOLFOX/bevacizumab then irinotecan then cetuximab/irinotecan and FOLFIRI/bevacizumab then FOLFOX then cetuximab/irinotecan were under the cost effectiveness curve. In addition no treatments ICER was under the WHO`s threshold for Turkey, except FOLFIRI then FOLFOX compared with FUVA.